Electrolyte and lithium battery

By using electrolyte containing fluoroether solvents in the lithium battery electrolyte, the cycling performance problem of medium-nickel high-voltage lithium batteries under high voltage operating conditions is solved, and better battery stability and performance are achieved.

CN119560629AActive Publication Date: 2025-03-04ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411793326.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Unstable substances in the electrolyte under high voltage conditions are easily decomposed, resulting in poor circulation performance.

Method used

An electrolyte solution including a fluoroether solvent is used, which contains a specific compound of formula (I) to improve the antioxidant performance and stability of the electrolyte.

Benefits of technology

The cycling performance of medium-nickel high-voltage lithium batteries is improved, the DC internal resistance growth rate under high-temperature storage conditions is reduced, and the long-term and stable operation of lithium batteries is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560629A_ABST
    Figure CN119560629A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and a lithium battery. The electrolyte comprises a fluoro-ether solvent, wherein the fluoroether solvent comprises at least one compound shown as a formula (I): # imgabs0 #, R2 is C4 alkylene or C4 fluoroalkylene, and the number of fluorine atoms in the C4 fluoroalkylene is 1; in the electrolyte, R1 and R3 are respectively and independently methyl or fluoromethyl, and the total number of fluorine atoms in R1 and R3 is 1-4, so that the electrolyte can improve the cycle performance of the medium-nickel high-voltage lithium battery, reduce the direct-current internal resistance growth rate under a high-temperature storage condition, and facilitate long-term stable operation of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of battery technology, and in particular to an electrolyte and a lithium battery. Background Art

[0002] Ternary positive electrode materials are a new type of positive electrode material for lithium batteries, such as nickel-cobalt-manganese, nickel-cobalt-aluminum, etc. Nickel-cobalt-manganese includes nickel salts, cobalt salts and manganese salts, which stand out from many positive electrode materials for lithium batteries with their higher operating voltage and greater energy density. Based on the proportion of nickel in nickel-cobalt-manganese, nickel-cobalt-manganese ternary positive electrode materials include low-nickel positive electrode materials, medium-nickel positive electrode materials and high-nickel positive electrode materials. Among them, the medium-nickel positive electrode material not only has a similar energy density effect to the high-nickel positive electrode material, but also has higher safety and lower cost. It is regarded as one of the mainstream solutions to solve the mileage anxiety of vehicle batteries. However, under high-voltage conditions, unstable substances in the electrolyte are very easy to decompose, resulting in poor cycle performance of medium-nickel high-voltage batteries. Summary of the invention

[0003] In view of this, the purpose of the present disclosure is to provide an electrolyte and a lithium battery.

[0004] Based on the above purpose, the first aspect of the present disclosure provides an electrolyte, comprising a fluoroether solvent; wherein the fluoroether solvent comprises at least one compound of formula (I):

[0005]

[0006] in,

[0007] R2 is C4 alkylene or C4 fluoroalkylene, wherein the number of fluorine atoms in the C4 fluoroalkylene is 1;

[0008] R1 and R3 are each independently a methyl group or a fluoromethyl group, and the total number of fluorine atoms in R1 and R3 is 1 to 4.

[0009] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the fluoroether solvent is 10% to 45%, optionally 15% to 35%.

[0010] In some embodiments, R2 is a C4 chain alkylene group or a C4 fluorinated chain alkylene group, optionally a C4 straight chain alkylene group or a C4 fluorinated straight chain alkylene group.

[0011] In some embodiments, a non-fluorinated ether solvent is also included; optionally, the non-fluorinated ether solvent includes at least one of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and carbonate, and more optionally ethylene glycol dimethyl ether.

[0012] In some embodiments, based on the total mass of the electrolyte, the mass fraction of ethylene glycol dimethyl ether is 40% to 75%, optionally 50% to 70%.

[0013] In some embodiments, the electrolyte further comprises a lithium salt; optionally, based on the total mass of the electrolyte, the mass fraction of the lithium salt is 11 to 15%, optionally 13 to 14%.

[0014] In some embodiments, the lithium salt includes at least one of LiPF6, LiBF4, LiClO4, LiCF3SO3, LiBOB, LiODFB, and LiN(SO2CF3)2; optionally, the lithium salt is LiPF6.

[0015] In some embodiments, the electrolyte further comprises at least one of lithium bis(fluorosulfonyl)imide, vinylene carbonate, and tetravinylsilane; optionally, based on the total mass of the electrolyte, the mass fraction of lithium bis(fluorosulfonyl)imide is 0.1% to 5%, more optionally 0.2% to 1%; optionally, the mass fraction of vinylene carbonate is 0.1% to 10%, more optionally 0.2 to 1%; optionally, the mass fraction of tetravinylsilane is 0.1% to 10%, more optionally 0.2% to 1%.

[0016] In some embodiments, the compound of formula (I) is selected from at least one of the following compounds:

[0017]

[0018]

[0019] Based on the same inventive concept, the second aspect of the present disclosure further provides a lithium battery, comprising the electrolyte described in any one of the foregoing; wherein, the positive electrode active material of the lithium battery comprises Li a Ni x Mn y Co z O2; wherein, 0.9 < a < 1.1, 0.5 < x < 0.7, 0.1 < z ≤ 0.2 and x + y + z = 1.

[0020] As can be seen from the above, for the electrolyte and lithium battery provided by the present disclosure, the electrolyte comprises a fluorinated ether solvent; wherein, the fluorinated ether solvent comprises at least one compound of formula (I): Among them, R2 is C4 alkylene or C4 fluoroalkylene, wherein the number of fluorine atoms in the C4 fluoroalkylene is 1; R1 and R3 are each independently methyl or fluoromethyl, and the total number of fluorine atoms in R1 and R3 is 1 to 4. Such an electrolyte can improve the cycle performance of medium-nickel high-voltage lithium batteries, reduce the DC internal resistance growth rate under high-temperature storage conditions, and is beneficial to the long-term stable operation of lithium batteries. DETAILED DESCRIPTION

[0021] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments.

[0022] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the embodiments of the present disclosure should have the common meanings understood by persons having ordinary skills in the field to which the present disclosure belongs.

[0023] The "range" used in the embodiments of the present disclosure is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 130 and 70 to 120 is listed for a particular parameter, it is understood that a range of 60 to 120 and 70 to 130 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present disclosure, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0024] If not otherwise specified, all embodiments and optional embodiments of the present disclosure may be combined with each other to form a new technical solution.

[0025] Unless otherwise specified, all technical features and optional technical features of the present disclosure can be combined with each other to form a new technical solution.

[0026] If there is no special explanation, the "include" and "comprising" mentioned in the present disclosure represent open or closed forms. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0027] If not specifically stated, in the present disclosure, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B".

[0028] In the related art, the solvent system of common lithium-ion battery electrolyte is mainly composed of a mixed solvent of cyclic carbonates and chain carbonates. Compared with ether solvents, cyclic carbonates and chain carbonates have better antioxidant properties, but they still have the risk of decomposition under high voltage conditions. Therefore, developing more diverse solvent molecular structures and giving lithium-ion battery electrolyte solvent systems more choices is a research hotspot.

[0029] Fluorinated ether solvents have both the higher solubility of ether solvents for lithium salts and a more stable chemical structure after modification with fluorine atoms, and are considered strong candidates for high-voltage battery electrolytes. However, due to the high viscosity and high cost of fluoroether solvents, it is difficult to use them as a single solvent system in lithium-ion batteries. In addition, due to the long carbon chain in the structure of fluoroethers, their solubility in common lithium salts is affected to a certain extent.

[0030] In order to achieve the purpose of the present disclosure, an embodiment of the present disclosure provides an electrolyte, which includes a new fluoroether solvent, which advantageously broadens the electrochemical working window of the electrolyte and improves the cycle performance of medium-nickel high-voltage batteries.

[0031] Electrolyte

[0032] The present disclosure provides an electrolyte solution, which includes a fluoroether solvent; wherein the fluoroether solvent includes at least one compound of formula (I):

[0033]

[0034] in,

[0035] R2 is C4 alkylene or C4 fluoroalkylene, wherein the number of fluorine atoms in the C4 fluoroalkylene is 1; here, alkylene refers to a saturated, branched or straight-chain, or cyclic hydrocarbon residue of 1 to 18 carbon atoms, and has two monovalent residue centers derived from the same carbon atom or two different carbon atoms of a parent alkane by removing two hydrogen atoms, for example, 1,4-butyl (-CH2CH2CH2CH2-).

[0036] R1 and R3 are each independently a methyl group or a fluoromethyl group, and the total number of fluorine atoms in R1 and R3 is 1 to 4.

[0037] The electrolyte provided by the present disclosure can improve the cycle performance of the medium nickel high voltage lithium battery and help the lithium battery to operate stably for a long time. Here, the lithium battery can be a primary lithium battery or a secondary lithium battery, which is not limited by the present disclosure.

[0038] The compound of formula (I) in the electrolyte disclosed in the present invention is an ether with a long carbon chain and containing at least one fluorine atom. After the fluorine atom is replaced, the charge density distribution of the compound itself is changed, and the more dispersed charge density distribution improves the oxidation resistance of the molecule, thereby improving the overall antioxidant performance of the electrolyte, and showing higher stability under high temperature cycle conditions. In addition, since the main chain of the compound (I) contains two oxygen atoms and the position is relatively symmetrical, this longer main chain solvent will not participate in the first solvent shell of the lithium ion, and therefore does not participate in film formation during the charge and discharge process, but after adding this type of fluoroether solvent, the components in the solvation structure of the lithium ion still change, so that relative to the battery without the addition of fluoroether solvents, its cycle stability is significantly improved, and the direct current resistance (Direct Current Resistance, referred to as DCR) growth rate of the 60-day high temperature storage test (High Temperature Storage Test, referred to as HTS) is reduced.

[0039] In some embodiments, R2 is a C4 chain alkylene group or a C4 fluorinated chain alkylene group, optionally a C4 straight chain alkylene group or a C4 fluorinated straight chain alkylene group.

[0040] In some embodiments, the compound of formula (I) is selected from at least one of the following compounds:

[0041]

[0042]

[0043] In some embodiments, the compound of formula (I) is selected from at least one of I-12, I-13, I-14, I-15, I-16, I-1, I-6, I-2, I-8, I-9, I-7, I-11, I-19 and I-5. In some embodiments, optionally, the compound of formula (I) is selected from at least one of I-11, I-12, I-13, I-14, I-16.

[0044] For the above compounds, the inventors found that although the oxidative stability of fluoroethers is relatively high, the difference in the number and position of fluorine substitutions causes the difference in the uniformity of the charge distribution of the overall structure of the compound, and the chemical stability of the structure also varies. The more uniform the charge distribution of the overall structure, the higher the corresponding oxidative stability, and the mixed electrolyte with ether solvents has better room temperature cycle performance. In addition, since the change in the fluoroether structure will affect the solvation structure of lithium ions in the electrolyte, it can also increase the stability of the electrolyte itself.

[0045] In some embodiments, the mass proportion of the fluoroether solvent is 10% to 45%, for example, 10%, 14%, 18%, 20%, 25%, 31%, 35%, 40%, 45%; optionally, 15% to 35%. If the mass range of the fluoroether solvent is less than 10%, the anti-oxidation stability of the solvent is insufficient, and it is difficult to improve the stability of the electrolyte. If the mass range of the fluoroether solvent is greater than 50%, the viscosity of the electrolyte will be too high and the number of cycles at room temperature will decrease. This may be because the DC internal resistance gradually increases during the cycle process, the internal polarization of the battery cell increases, and the performance of the number of cycles at room temperature of the battery cell deteriorates.

[0046] In some embodiments, the electrolyte further comprises a non-fluorinated ether solvent. Optionally, the non-fluorinated ether solvent comprises at least one of tetrahydrofuran (THF), ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), tetraethylene glycol dimethyl ether (G4) and carbonate, more optionally ethylene glycol dimethyl ether.

[0047] It should be noted that carbonates include cyclic carbonates and chain carbonates. Exemplarily, cyclic carbonate solvents include at least one of propylene carbonate (PC) and ethylene carbonate (EC). Optionally, cyclic carbonate solvents are ethylene carbonate. Cyclic carbonate solvents have a higher dielectric constant, which helps to dissolve lithium salts and evenly distribute them in the electrolyte, thereby ensuring the normal operation of the battery. In addition to increasing the solubility of lithium salts, ethylene carbonate can also form a stable solvation configuration with lithium ions, improve the stability and conductivity of the electrolyte, thereby improving the performance of the lithium battery. Exemplarily, the chain carbonate solvent includes at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The electrolyte includes a chain carbonate solvent, which can reduce the overall viscosity and help improve the conductivity, cycle life and energy density of the lithium battery.

[0048] In some embodiments, the electrolyte includes ethylene carbonate and ethyl methyl carbonate. Further, based on the total mass of the electrolyte, the mass proportion of ethylene carbonate is 15% to 25%; the mass proportion of ethyl methyl carbonate is 40% to 60%. The combination of ethylene carbonate and ethyl methyl carbonate is conducive to ensuring the solubility of the solvent in the lithium salt while controlling the viscosity of the electrolyte, thereby obtaining a high-performance lithium battery.

[0049] In some embodiments, based on the total mass of the electrolyte, the mass proportion of ethylene glycol dimethyl ether is 40% to 75%, and optionally 50% to 70%. The electrolyte includes ethylene glycol dimethyl ether and the compound represented by formula (I) in the above range, which helps to improve room temperature cyclability and high temperature storage performance, and is particularly suitable for use with medium nickel positive electrode active materials.

[0050] In some embodiments, the electrolyte further comprises a lithium salt; optionally, based on the total mass of the electrolyte, the mass proportion of the lithium salt is 11% to 15%, optionally 13% to 14%.

[0051] In some embodiments, the lithium salt includes at least one of LiPF6, LiBF4, LiClO4, LiCF3SO3, LiBOB, LiODFB, and LiN(SO2CF3)2.

[0052] Optionally, the lithium salt is LiPF6. LiPF6 has good solubility in a mixture of a non-fluorinated ether solvent and a fluorinated ether solvent, thereby avoiding the degradation of battery performance caused by insufficient solubility of the lithium salt.

[0053] In some embodiments, the electrolyte further comprises an additive, and optionally, the additive is selected from at least one of lithium bis(fluorosulfonyl)imide (LiFSI), vinylene carbonate (VC) and tetravinylsilane (TVSi); optionally, the additive comprises lithium fluorosulfonyl imide (LiFSI), vinylene carbonate (VC) and tetravinylsilane (TVSi); more optionally, the additive comprises vinylene carbonate (VC) and tetravinylsilane (TVSi). Lithium fluorosulfonyl imide helps to increase the lithium ions in the electrolyte, thereby improving the overall performance of the battery; the combination of vinylene carbonate and tetravinylsilane (TVSi) will generate a relatively polymerized network of solid electrolyte interface film layers (SEI and CEI) on the surface of the positive and negative electrodes, which will protect the positive and negative electrode materials during the cycle process, and is conducive to improving the cycle performance of the battery cell.

[0054] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the lithium bis(fluorosulfonyl)imide is 0.1% to 5%, and more optionally 0.2% to 1%; optionally, the mass proportion of the vinylene carbonate is 0.1% to 10%, and more optionally 0.2% to 1%; optionally, the mass proportion of the tetravinylsilane is 0.1% to 10%, and more optionally 0.2% to 1%.

[0055] Lithium battery

[0056] A second aspect of the present disclosure provides a lithium battery, comprising the electrolyte provided in the above disclosure.

[0057] In some embodiments, the lithium battery includes a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0058] Positive electrode

[0059] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0060] Exemplarily, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0061] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (e.g., polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0062] In some embodiments, the positive electrode active material includes lithium nickel cobalt manganese oxide, such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5Co 0.25 Mn 0.25 O2 (which can also be abbreviated as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (which can also be abbreviated as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (which can also be abbreviated as NCM811).

[0063] Optionally, the positive electrode active material of the lithium battery includes Li a Ni x Mn y Co z O2; wherein, 0.9 < a < 1.1, 0.5 < x < 0.7, 0.1 < z ≤ 0.2 and x + y + z = 1. When 0.5 < x < 0.7, the electrochemical performance of the positive electrode active material is excellent; when x > 0.7, the stability of the positive electrode active material is poor, and there may be oxidation of the fluorinated ether solvent on the surface of the positive electrode during charge and discharge. The unstable solvent system makes it difficult to operate stably for a long time due to the diving in the later stage of cycling at 25°C. This may be because a film layer is formed on the surface of the positive electrode after the fluorinated ether undergoes an oxidation reaction, and the poor conductivity of this film layer leads to an increase in the DC internal resistance, which can be corroborated by the increase rate of the DC internal resistance in the high-temperature storage test.

[0064] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0065] In some embodiments, the positive electrode film layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0066] In some embodiments, the positive electrode plate can be prepared in the following manner: Disperse the components for preparing the positive electrode plate, such as the positive electrode active material, conductive agent, binder, and any other components, in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; coat the positive electrode slurry on the positive electrode current collector, and after processes such as drying and cold pressing, the positive electrode plate can be obtained.

[0067] Negative electrode

[0068] The negative electrode sheet includes a negative electrode current collector and a film layer optionally disposed on at least one surface of the negative electrode current collector.

[0069] Exemplarily, the film layer may include a negative electrode active material (eg, artificial graphite), a conductive agent, a thickener, and a binder.

[0070] In some embodiments, the negative electrode sheet can be prepared in the following manner: the negative electrode active material, the conductive agent, the thickener, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0071] Isolation film

[0072] In some embodiments, the secondary battery further includes a separator. The present disclosure has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0073] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0074] Example

[0075] Hereinafter, embodiments of the present disclosure are described. The embodiments described below are exemplary and are only used to explain the present disclosure, and should not be construed as limiting the present disclosure. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in the art or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0076] Example 1 to Example 14

[0077] Embodiments 1 to 14 of the present disclosure are secondary lithium batteries, wherein the positive electrode active material is a medium nickel high voltage positive electrode material, and the specific preparation method thereof is as follows:

[0078] (1) LiNi 0.6 Mn 0.3 Co 0.1 Preparation of O2 positive electrode:

[0079] The positive electrode active material LiNi 0.6 Mn 0.3 Co 0.1O2, polyvinylidene fluoride as a binder, and conductive carbon black (Super P) as a conductive agent are mixed in a weight ratio of 98:1:1, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the system becomes uniform and transparent to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil; the aluminum foil is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode (positive electrode sheet);

[0080] (2) Preparation of graphite negative electrode:

[0081] Artificial graphite is used as the negative electrode active material, Super P is used as the conductive agent, sodium carboxymethyl cellulose (CMC-Na) is used as the thickener, and styrene-butadiene rubber (SBR) is used as the binder, which are mixed in a mass ratio of 96:1:1:2, and deionized water is added to obtain the negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the copper foil is dried at room temperature and then transferred to an oven for drying, and then the negative electrode (pole sheet) is obtained through cold pressing and slitting.

[0082] (3) Preparation of electrolyte:

[0083] In an argon atmosphere glove box with a water content of <10 ppm, battery-grade fluoroether I-12, ethylene glycol dimethyl ether (DME), tetrahydrofuran (THF), triethylene glycol dimethyl ether (G3), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed according to the proportions in Examples 1 to 14 to form a total organic solvent. VC, TVSi, LiPF6, and LiFSI are mixed evenly with the above-mentioned organic solvents according to the proportions in Examples 1 to 14 to obtain an electrolyte.

[0084] The proportions of the components in Examples 1 to 14 are shown in Table 1. It should be noted that the content of each component in Table 1 is the mass percentage calculated based on the total mass of the electrolyte.

[0085] (4) Preparation of isolation membrane:

[0086] Polypropylene film is used as the isolation film.

[0087] (5) Preparation of secondary batteries:

[0088] A 12 μm thick polypropylene film was used as a separator, and the positive electrode, separator, and negative electrode prepared above were stacked in sequence, so that the separator was placed between the positive and negative electrodes to play a role of isolation. Then, an aluminum-plastic film was wrapped outside, transferred to a vacuum oven for drying at 120°C, and the electrolyte prepared above was injected at 3.0 g / Ah, and then sealed, and the electrolyte was formed, and finally a soft-pack battery (i.e., a lithium-ion battery) with a capacity of 1 Ah was prepared.

[0089] Comparative Example 1 to Comparative Example 4

[0090] Comparative Examples 1 to 4 are different from Example 1 in that the organic solvent composition in step (3) is used. The components and proportions of the organic solvents in Comparative Examples 1 to 4 are shown in Tables 1 and 2. In Table 2, A represents the compound represented by formula A B represents a compound of formula B

[0091] Example 15, Comparative Example 5

[0092] Example 15, Comparative Example 5 and Example 1 are different in that step (1): the positive electrode active material is replaced with LiNi 0.9 Mn 0.05 Co 0.05 The composition and proportion of the organic solvent in step (3) are shown in Table 2.

[0093] Test Method

[0094] The secondary batteries prepared in the above embodiments and comparative examples can be tested by the following method:

[0095] (1) Secondary battery high temperature storage test

[0096] In an oven at a specified temperature (high temperature 45°C), the battery is charged at a current of 0.2C in a specified potential range (2.0V~3.8V), and discharged at a current of 1C in a specified potential range (2.8V~4.35V). After three cycles of charge and discharge, the initial volume of the battery cell is measured and recorded as V0. The battery is stored in an oven at a specified temperature (high temperature 60°C) for a fixed time interval (60d), and the DCR is measured at each time interval. The high-temperature storage DCR growth rate is calculated by the difference between DCR 0d and DCR 60d. The test results are detailed in Tables 1 and 2.

[0097] (2) Secondary battery cycle test at room temperature

[0098] In an oven at a specified temperature (25°C), cyclic charge and discharge were performed at a current of 1C in a specified potential range (2.0V-3.8V), and the discharge capacity of each cycle was recorded. The test was terminated when the battery capacity reached 80% of the first cycle capacity. The test results are detailed in Tables 1 and 2.

[0099] Table 1

[0100]

[0101] Table 2

[0102]

[0103] Comparing Comparative Examples 1 to 4 and Example 6, it can be seen that adding a fluoroether solvent to the electrolyte, whether it is fluoroether I-12, or octafluoropentyl-tetrafluoroethyl ether, formula A or formula B, can improve the stability of the normal temperature cycle of the battery and reduce the DC internal resistance growth rate under high temperature storage conditions. Comparing Comparative Examples 2 to 4 and Example 6, it can be seen that different fluoroether solvents have a large difference in the improvement effect of the normal temperature battery cycle stability and the DC internal resistance growth rate. The fluoroether I-12 provided in the embodiment of the present disclosure has a significantly better improvement effect on the normal temperature battery cycle stability than octafluoropentyl-tetrafluoroethyl ether, formula A and formula B. This may be because when the fluoroether compound provided in the present disclosure is combined with ethylene glycol dimethyl ether (DME) as an organic solvent, the electrolyte has good stability and can provide good lithium salt dissolution performance, thereby improving the battery cycle performance at room temperature and reducing the DC internal resistance growth rate.

[0104] Comparison of Comparative Example 1, Examples 1 to 2, Examples 5 to 7, and Examples 9 to 10 shows that the addition of fluoroether I-12 to the electrolyte can improve the cycle stability of the battery cell and reduce the DC internal resistance growth rate under high temperature storage conditions. In particular, when the mass proportion of fluoroether I-12 is within the range of 15% to 35%, the addition of fluoroether I-12 significantly improves the cycle stability of the battery cell and reduces the DC internal resistance growth rate.

[0105] Comparing Example 6 with Example 11 to Example 13, it can be found that compared with the combination of THF, G3, carbonate and fluoroether I-12, the combination of DME and fluoroether I-12 is more conducive to improving the cycle stability of the battery. This may be because G3 is not substituted by fluorine atoms and has a long chain and a large number of ether bonds, and THF is a ring structure, which is not thermodynamically stable enough. During the cycle, it will decompose into film-forming substances that are not conducive to lithium ion conduction on the negative electrode, resulting in poor performance of batteries including THF and G3. DME is highly stable, not easily oxidized or reduced, and has good solubility in lithium salts. It can cooperate with fluoroether I-12 to solve the problem of insufficient solubility of fluoroether I-12 in lithium salts, thereby improving the performance of the battery.

[0106] Comparing Example 15, Comparative Example 5 and Example 6, it can be seen that fluoroether I-12 can also improve the cycle stability of the battery cells prepared with high-nickel cathode active materials and reduce the growth rate of DC internal resistance. At the same time, the cathode active material also has a relatively large impact on the cycle stability of the battery cells. Compared with the high-nickel cathode active materials (Example 15 and Comparative Example 5), the battery cell performance is better when fluoroether I-12 is paired with the medium-nickel cathode active material (Ni6 in Example 6). This may be because the material stability of the high-nickel cathode is poor, and there may be a situation where fluoroether is oxidized on the surface of the cathode during charge and discharge. The unstable solvent system causes the number of room-temperature cycles to drop sharply in the later stage of the cycle. After the fluoroether undergoes an oxidation reaction, a film-forming substance is generated on the surface of the cathode, and the poor ionic conductivity of this layer of substance leads to a high growth rate of HTS-DCR 60d. Except for fluoroether I-12, when the compounds of formula (I) are paired with the high-nickel cathode materials, similar results are shown and will not be elaborated further.

[0107] It should be noted that the cathode active materials of Comparative Example 1 and Examples 1 to 14 are only representatives of medium-nickel cathode active materials, rather than limitations. The medium-nickel cathode active material of the present disclosure refers to Li a Ni x Mn y Co z O2; wherein, 0.9 < a < 1.1, 0.5 < x < 0.7, 0.1 < z ≤ 0.2 and x + y + z = 1.

[0108] Comparing Example 3, Example 4, Example 6, Example 8 and Example 14, it can be seen that adding LiFSI or the combination of LiFSI, VC and TVSi to the electrolyte can improve the cycle performance of the battery cells and reduce the growth rate of DC internal resistance. In particular, the combined use of VC and TVSi will form a relatively dense SEI and CEI on the surfaces of the positive and negative electrodes, which will play a protective role for the positive and negative electrode materials during the cycle and is beneficial to improving the cycle performance of the battery cells.

[0109] Example 16 to Example 23

[0110] The preparation methods of Examples 16 to 23 are similar to those of Examples 1 to 10, except that fluoroether I-12 is replaced by fluoroether I-16. The detailed compositions and test results of the electrolytes are shown in Table 3.

[0111] Table 3

[0112]

[0113] Example 24 to Example 31

[0114] The preparation methods of Examples 24 to 31 are similar to those of Examples 1 to 10, except that the fluoroether I-12 is replaced by the fluoroether I-15. The detailed composition and test results of the electrolyte are shown in Table 4.

[0115] Table 4

[0116]

[0117] Example 32 to Example 39

[0118] The preparation methods of Examples 32 to 39 are similar to those of Examples 1 to 10, except that fluoroether I-12 is replaced by fluoroether I-8. The detailed composition and test results of the electrolyte are shown in Table 5.

[0119] Table 5

[0120] category DME Fluoroether I-8 <![CDATA[LiPF6]]> LiFSI VC TVSi HTS-DCR 60d growth rate Cycle times at 25℃ Embodiment 32 43.25 43.25 13 0.5 — — 0.14 1292 Embodiment 33 60.20 25.80 13 0.5 0.5 — 0.12 1838 Embodiment 34 60.41 25.89 13 0.5 — 0.2 0.11 1873 Embodiment 35 69.20 17.30 13 0.5 — — 0.10 1724 Embodiment 36 60.55 25.95 13 0.5 — — 0.09 1799 Embodiment 37 51.90 34.60 13 0.5 — — 0.09 1929 Embodiment 38 60.06 25.74 13 0.5 0.5 0.2 0.09 2125 Embodiment 39 76.50 10.00 13 0.5 — — 0.13 1420

[0121] Embodiment 40 to Embodiment 47

[0122] The preparation methods of Examples 40 to 47 are similar to those of Examples 1 to 10, except that the fluoroether I-12 is replaced by the fluoroether I-19. The detailed composition and test results of the electrolyte are shown in Table 6.

[0123] Table 6

[0124]

[0125] Embodiment 48~embodiment 55

[0126] The preparation methods of Examples 48 to 55 are similar to those of Examples 1 to 10, except that the fluoroether I-12 is replaced by the fluoroether I-11. The detailed composition and test results of the electrolyte are shown in Table 7.

[0127] Table 7

[0128]

[0129]

[0130] Embodiment 56 to Embodiment 63

[0131] The preparation methods of Examples 56 to 63 are similar to those of Examples 1 to 10, except that the fluoroether I-12 is replaced by the fluoroether I-7. The detailed composition and test results of the electrolyte are shown in Table 8.

[0132] Table 8

[0133]

[0134] Embodiment 64 to Embodiment 71

[0135] The preparation methods of Examples 64 to 71 are similar to those of Examples 1 to 10, except that fluoroether I-12 is replaced by fluoroether I-1. The detailed composition and test results of the electrolyte are shown in Table 9.

[0136] Table 9

[0137]

[0138] Example 72 to Example 79

[0139] The preparation methods of Examples 72 to 79 are similar to those of Examples 1 to 10, except that fluoroether I-12 is replaced by fluoroether I-2. The detailed composition and test results of the electrolyte are shown in Table 10.

[0140] Table 10

[0141]

[0142] Embodiment 80 to Embodiment 87

[0143] The preparation methods of Examples 80 to 87 are similar to those of Examples 1 to 10, except that fluoroether I-12 is replaced by fluoroether I-5. The detailed composition and test results of the electrolyte are shown in Table 11.

[0144] Table 11

[0145]

[0146] It can be seen from the test results of Tables 1 to 11 that adding the compound of formula (I) provided by the embodiments of the present disclosure to the electrolyte can improve the cycle stability of the battery cell and reduce the increase rate of the DC internal resistance under high temperature storage conditions. Adding LiFSI, VC and TVSi to the electrolyte can further improve the cycle stability of the battery cell.

[0147] In addition, the electrolyte provided in the embodiments of the present disclosure is particularly suitable for medium-nickel high-voltage positive electrode active materials, which facilitates the preparation of lithium batteries with high energy density, good safety and low cost.

[0148] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present disclosure (including the claims) is limited to these examples. Based on the concept of the present disclosure, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the embodiments of the present disclosure as described above, which are not provided in detail for the sake of simplicity.

[0149] The embodiments of the present disclosure are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present disclosure should be included in the scope of protection of the present disclosure.

Claims

1. An electrolyte, characterized in that: Including fluoroether solvents; wherein the fluoroether solvent includes at least one compound of formula (I): in, R2 is C4 alkylene or C4 fluoroalkylene, wherein the number of fluorine atoms in the C4 fluoroalkylene is 1; R1 and R3 are each independently a methyl group or a fluoromethyl group, and the total number of fluorine atoms in R1 and R3 is 1 to 4.

2. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the mass proportion of the fluoroether solvent is 10% to 45%, and optionally 15% to 35%.

3. The electrolyte according to claim 1 or 2, characterized in that R2 is a C4 chain alkylene group or a C4 fluorinated chain alkylene group, and may be a C4 straight chain alkylene group or a C4 fluorinated straight chain alkylene group.

4. The electrolyte according to any one of claims 1 to 3, characterized in that Also included are non-fluorinated ether solvents; the non-fluorinated ether solvents include at least one of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and carbonate.

5. The electrolyte according to claim 4, characterized in that The non-fluorinated ether solvent includes ethylene glycol dimethyl ether; Based on the total mass of the electrolyte, the mass proportion of the ethylene glycol dimethyl ether is 40% to 75%.

6. The electrolyte according to claim 5, characterized in that Based on the total mass of the electrolyte, the mass proportion of the ethylene glycol dimethyl ether is 50% to 70%.

7. The electrolyte according to any one of claims 1 to 6, characterized in that The electrolyte further includes a lithium salt, wherein the lithium salt includes at least one of LiPF6, LiBF4, LiClO4, LiCF3SO3, LiBOB, LiODFB and LiN(SO2CF3)2; Based on the total mass of the electrolyte, the mass proportion of the lithium salt is 11% to 15%.

8. The electrolyte according to any one of claims 1 to 7, characterized in that The electrolyte also includes at least one of lithium bis(fluorosulfonyl)imide, vinylene carbonate and tetravinylsilane; optionally, based on the total mass of the electrolyte, the mass proportion of the lithium bis(fluorosulfonyl)imide is 0.1% to 5%, more optionally 0.2% to 1%; optionally, the mass proportion of the vinylene carbonate is 0.1% to 10%, more optionally 0.2% to 1%; optionally, the mass proportion of the tetravinylsilane is 0.1% to 10%, more optionally 0.2% to 1%.

9. The electrolyte according to any one of claims 1 to 8, characterized in that The compound of formula (I) is selected from at least one of the following compounds:

10. A lithium battery comprising the electrolyte according to any one of claims 1 to 9; wherein: The positive electrode active material of the lithium battery includes Li a Ni x Mn y Co z O2; wherein, 0.9 < a < 1.1, 0.5 < x < 0.7, 0.1 < z ≤ 0.2 and x + y + z = 1.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte and lithium ion battery prepared therefrom

    CN102496737A

  • A non-aqueous electrolyte for a lithium ion battery and a lithium ion battery using the electrolyte

    CN109148960A

  • Electrolyte, and electrochemical apparatus comprising same

    CN109301322A

  • Solvent for nonaqueous electrolyte of lithium secondary battery

    JP2010238510A

  • Electrolyte and lithium-ion battery containing the same

    US20170346136A1